Performance evaluation of Malaysia Official Government Tourism websites using web diagnostic tools: a Malaysian case / Faraheeda Ishak - Ishak, Faraheeda (2013)
Nowadays, most people are heavily relying on the Internet specifically the websites to acquire information to make prompt decision. As a user, the access to Internet has becoming easier through various medium of mobility devices such as smartphones, tablets and laptops. And because of the advancement in technology devices, the users are expecting a good quality websites for them to access. Malaysia Official Government Tourism Websites are among the many websites that users normally visit to seek for tourism information in Malaysia. According to their feedback, they are mostly interested to visit a website that could provide reliable information and most importantly response to their requests in a reasonable amount of time. They will not wait patiently for the website to load hence they would abandoned the website and look for another one instead. Thus, the website quality, its performance and reliability are crucial towards the improvement of the website experience. Therefore, the main objective of this study is to evaluate the performance and quality of 18 Malaysia Official Government Tourism Websites using Web Diagnostic Tools based on research model adapted from Dominic and Jati (2009). According to Dominic and Jati (2009), website quality performance can be measure using 10 evaluation criteria such as Average Server Response Time, Website Load Time, Website Size, and Number of Items per page, HTML Code Validity, Broken Link, Accessibility, Website Optimization, Link Popularity and Colour Blind. The data was gathered using 8 Web Diagnostic Tools such as Website Optimization.com, Website Pulse, W3C HTML Mark-up Validator, Any Browser - Link Checker, Web Page Test, Vischeck, Link Popularity and TAWDIS and the reported data are analyses using IBM Standard of the website performance. Based on the overall performance has highlighted that the best performance website is Kelantan Tourism. It also highlights that among the 10 evaluation criteria category, there are 4 common criteria that the web designer and web developer need to look into to improve their websites performance. The 4 criteria are HTML Code Validity, Average Server Response Time, Accessibility and Website Optimization. With this, this study has confirmed that Malaysia Official Government Tourism Websites are neglecting performance and quality criteria. Hence, this report has provides recommendation on ways to improve the performance of Malaysia Official Government Tourism Websites.